Kaderisasi Ulama Pada Islamic Center Wadi Mubarak Megamendung Bogor (Elkid) - Musleh Wahid; Ishlahuddin Ishlahuddin (Fakta: Jurnal Pendidikan Agama Islam, 2021)
The findings in this study prove that the Imam as a leader must also be able to invite his congregation to have a good attitude in religion and state and keep them away from actions that can harm others. Therefore it is necessary to do the cadre of prayer priests who are also preachers who understand religion and the State through holistic Islamic education. The problems that are the focus of this research are: How is the implementation of cadre education at the Institute for Cadre of Imams and Dai (eLKID) Islamic Center Wadi Mubarak Megamendung Bogor? and What is the role of Ustadz in the implementation of cadre education at the Islamic Center Wadi Mubarak Megamendung Bogor Cadre of Imam and Dai (eLKID) Institute? This research uses a case study qualitative research approach. Through interviews, observation and documentation. From this method, then the researcher analyzed with data reduction, then presented and concluded the conclusion. The subjects of this research were obtained from the leaders and carers of the institution and several Ustadz who were actively teaching at the institution. For data validity, researchers used source triangulation and methods of comparing the results of interviews with observations and documentation. Ustadz The role in the implementation of cadre education includes education, cultivating, guiding, guiding, being role models, mentoring and supervision for 24 hours a day.